All-trans-retinal dimer formation alleviates the cytotoxicity of all-trans-retinal in human retinal pigment epithelial cells. (14th September 2016) - Li, Jie; Zhang, Yanli; Cai, Xianhui; Xia, Qingqing; Chen, Jingmeng; Liao, Yi; Liu, Zuguo; Wu, Yalin
Abstract: Effective clearance of all- trans -retinal (atRAL) from retinal pigment epithelial (RPE) cells is important for avoiding its cytotoxicity. However, the metabolism of atRAL in RPE cells is poorly clarified. The present study was designed to analyze metabolic products of atRAL and to compare the cytotoxicity of atRAL versus its derivative all- trans -retinal dimer (atRAL-dimer) in human RPE cells. We found that all- trans -retinol (atROL) and a mixture of atRAL condensation metabolites including atRAL-dimer and A2E were generated after incubating RPE cells with atRAL for 6 h, and the amount of atRAL-dimer was significantly higher than that of A2E. In the eyes of Rdh8 −/− Abca4 −/− mice, a mouse model with defects in retinoid cycle that displays some symbolic characteristics of age-related macular degeneration (AMD), the level of atRAL-dimer was increased compared to wild-type mice, and was even much greater than that of A2E & isomers. The cytotoxicity of atRAL-dimer was reduced compared with its precursor atRAL. The latter could provoke intracellular reactive oxygen species (ROS) overproduction, increase the mRNA expression of several oxidative stress related genes ( Nrf2, HO-1, and γ-GCSh ), and induce ΔΨ m loss in RPE cells. By contrast, the abilities of atRAL-dimer to induce intracellular ROS and oxidative stress were much weaker versus that of concentration-matched atRAL, and atRAL-dimer exhibited no toxic effect on mitochondrial function at higher concentrations. In conclusion, the formation of atRAL-dimer during atRAL metabolic process ameliorates the cytotoxicity of atRAL by reducing oxidative stress.